Strategi Pengembangan Budaya Mutu dalam Meningkatkan Kualitas Unggul pada Lembaga Madrasah Ibtidaiyah di Indonesia - Faridah, Zeni (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAI Senori Tuban, 2024)
Quality culture is an assessment system of an organization that produces an environmental condition that is conducive to the formation of continuous improvement in terms of quality. Quality culture is the key to achieving excellence in educational quality, in relation to the strategy for developing a quality culture in improving superior quality at Madrasah Ibtidaiyah Institutions in Indonesia. This research uses a type of library research research by collecting data and information with the help of various materials contained in the literature (books) with relevant research results. The research results show that developing a culture of quality is an important aspect in educational institutions as the main key to success in optimal and sustainable learning outcomes in improving quality. Teaching staff, facilities and infrastructure, and learning programs are also a culture of quality that must be planned well. By paying attention to curriculum aspects, the madrasa teaching profession can continue to improve superior quality in developing a culture of quality education in Indonesia. The role of all stakeholders is also important in the success of improving a quality culture, this is because solidarity and work discipline are the main roles in building a good institution. Challenges that arise in improving the superior quality of quality culture in Madrasah Ibtidaiyah institutions are seen from the leadership of principals, educators, involvement of parents, and the community in building cooperation in the process of developing a sustainable quality culture.